Formation of Temperature Mode in Internal Spaces of Armored Machinery - P. I. Dziachek; A. S. Mezentsev (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
An algorithm and a program  have been developed for calculation of temperature mode in a T-72 tank tower while using numerical methods. The paper reveals a satisfactory convergence of calculated and experimental data. The results pertaining to investigation of influence of various factors on the processes of temperature mode formation in the internal surfaces of the studied object are presented in the paper. The obtained results make it possible to develop technical solutions in respect of protection against condensation of water vapor on the internal surfaces of armored machinery.